INNOVATIVE LEADERSHIP OF ADMINISTRATORS AFFECTING THE EFFECTIVENESS OF PERSONNEL MANAGEMENT IN SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE UDON THANI - Sarapon, Boriphat; Steannoppakao , Pornthep; Somsrisuk, Apisit (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The purposes of this research were to examine: 1) the level of school administrators’ innovative leadership, 2) the effectiveness level of personnel management in schools, 3) the relationship between school administrators’ innovative leadership and the effectiveness of personnel management in schools, and 4) school administrators’ innovative leadership affecting the effectiveness of personnel management in schools under the Secondary Educational Service Area Office Udon Thani. The sample, obtained through multi-stage sampling, consisted of school administrators and teachers working in schools under the Secondary Educational Service Area Office Udon Thani in the 2021 academic year, yielding a total of 359 participants. The research instrument consisted of a set of 5-level rating scale questionnaires, including school administrators’ innovative leadership, with discriminative power values ranging from 0.53 to 0.71, and the reliability of 0.95; and the effectiveness of personnel management in schools, with discriminative power values ranging from 0.50 to 0.70, and the reliability of 0.94. Statistics for data analysis included percentage, mean, standard deviation, Pearson’s product–moment correlation coefficient, and Stepwise multiple regression analysis. The findings were as follows: 1) The school administrators’ innovative leadership, overall and in each aspect, was at a high level, 2) The effectiveness of the personnel management in schools, overall and in each aspect, was at a high level, 3) The relationship between school administrators’ innovative leadership and the effectiveness of personnel management in schools showed a positive correlation with a moderate level at the .01 level of significance, and 4) The school administrators’ innovative leadership comprising transformational vision and creation of innovative organizations jointly predicted the effectiveness of personnel management in schools at the .01 level of significance, with 26.10 percent of the variance, and could be written in the regression equation in the form of the standardized scores as follows: